ULASAN METODOLOGI KUALITATIF: WAWANCARA TERHADAP ELIT - Hakim, Lukman Nul (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2013)
In the past two decades literature studies on elite has emerged even though still small in number. Elites are people who because of his/her position or role and can influence decisions concerning the lives of many people. Therefore every behavior, decision making and mindset of elite is an interesting subject to be studied in a deeper level. But in reality making elite as research subject provide challenges. Among the many approaches to qualitative methods, interviewing techniques most widely used to assess the elite, therefore this article discusses the challenges that will be faced by researchers when interviewing elites. Starting from the things that must be prepared before the researchers conducted interviews, during the interview, and after the interview. With good preparation then the research process can be optimized.